OP0234 Association between ultrasound colour doppler activity and synovial pathology in biopsies from small hand joints in patients with rheumatoid arthritis: A cross sectional study. (23rd January 2014) - Andersen, M.; Ellegaard, K.; Hebsgaard, J.; Christensen, R.; Kvist, P.H.; Vendel, N.; Rømer, J.; Søe, N.; Bliddal, H.
Abstract : Background: Little is known regarding the association between ultrasound determined pathological synovial blood flow and synovial pathology in rheumatoid arthritis (RA). Objectives: To examine the association between colour Doppler ultrasound imaging and synovitis according to histopathology in patients with RA. Methods: 51 synovial sites from the small hand joints from 19 RA patients were evaluated by ultrasound colour Doppler and subsequently biopsied by needle arthroscopy. Association between ultrasound colour fraction and an overall synovitis score (1) and immunohistochemical stainings for CD3, CD68, Ki67 and von Willebrandt Factor were investigated (2;3) using repeated samples from the same patients. The overall synovitis score (total 0-9) assessed synovial hypertrophy (0-3), stromal proliferation (0-3) and cellular infiltration (0-3). Data was clustered within patients, thus a linear mixed model was applied for the statistical analysis. Parsimony in the statistical models was achieved omitting covariates from the model in the case of, what was judged, no statistical significance (P>0.1). Results: For the RA patients Doppler colour fraction showed an association with the overall synovitis score (Approximated Spearman, Appr.rho =0.43, P=0.002). The density of all immunohistochemical staining showed a significant association with Doppler colour fraction: von Willebrandt Factor (Appr.rho =0.49, P=0.01), CD68 (Appr.rho=0.49, P=0.0002, ), Ki67 (Appr.rho =0.47, P=0.002) and CD3 (Appr.rho=0.66, P<0.0001). Conclusions: Colour Doppler activity significantly correlates with the extent of inflammation present in the synovium of RA patients. Absence of a detectable colour fraction does not rule out synovial pathology. Acknowledgement: Supported by unrestricted grants from Novo Nordisk and the Oak Foundation. B. Jørgensen for preparation of the synovial biopsies. References: Krenn V et al.Grading of chronic synovitis–a histopathological grading system for molecular and diagnostic pathology. Pathol Res Pract 2002;198(5):317-25. Ogdie A et al. Identification of broadly discriminatory tissue biomarkers of synovitis with binary and multicategory receiver operating characteristic analysis. Biomarkers 2010 March;15(2):183-90 Pessler F et al. The synovitis of "non-inflammatory" orthopaedic arthropathies: a quantitative histological and immunohistochemical analysis. Ann Rheum Dis 2008 August;67(8):1184-7. Disclosure of Interest: M. Andersen Employee of: Novo Nordisk A/S, K. Ellegaard: None Declared, J. Hebsgaard Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, R. Christensen: None Declared, P. Kvist Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, N. Vendel: None Declared, J. Rømer Shareholder of: Novo Nordisk A/S, Employee of: Novo Nordisk A/S, N. Søe: None Declared, H. Bliddal: None Declared